Assessment of reaction patterns of hybrids to Striga hermonthica (Del.) Benth. under artificial infestation in Kenya and Nigeria - Menkir, A.; Makumbi, Dan; Franco, J. (Wiley, 2012)
Striga hermonthica (Del.) Benth. is a widespread parasitic weed that infl icts damage on maize (Zea mays L.) in sub-Saharan Africa. This is a highly variable root parasite that can contribute to signifi cant genotype × parasite population interaction observed in field trials. The present study was thus conducted to determine the reaction patterns of hybrids developed in Nigeria for field resistance to S. hermonthica under artifi cial infestation at two locations eachin Kenya and Nigeria in 2009 and 2010. In the combined analysis of variance, mean squares for country, location (country), year × country, hybrid × year × country, and hybrid × location (country) interactions were not signifi cant for all measured traits. The variance for year, hybrid, year × location (country), hybrid × year, hybrid × country, and hybrid × year × location (country) interactions were signifi cant for some or all measured traits. The nonparametric tests of concordance was signifi cant (p < 0.0001) for all traits recorded under infestation in eight test environments (W = 0.55 to W = 0.76) in the two countries, indicating that S. hermonthica–resistant hybrids developed in Nigeria were also resistant in Kenya. Pattern analysis using a three-way clustering method separated the 16 maize hybrids into two distinct groups with similar reaction patterns and levels of performance in the prevalent test environments of the two countries. Resistant hybrids had higher grain yields, fewer Striga damage symptoms, fewer emerged parasites, and taller plants in comparison to the tolerant, susceptible, and commercial hybrid checks. Some hybrids with consistent levels of resistance to S. hermonthica across locations and seasons in the two countries were identifi ed in this study for further testing under a broad range of production conditions in the Striga-affected areas of Kenya, Nigeria, and other countries to select the best hybrids for eventual release.